Reverse dot blot hybridization assay— An expeditious diagnostic tool for drug resistant TB - Faeez Muhammad; Siddiqui, Laiba; Gul, Rabbia (Journal of the Pakistan Medical Association, 2022)
Tuberculosis (TB) is one of the leading infectious diseases that is highly transmissible. It is reported to cause approximately 10 million infections and 1.4 million deaths globally in the year of 2019.¹ Prompt detection and treatment of TB are essential to intercept the proliferation of the disease. In the case of drug- resistant TB, failure to detect the resistance of anti TB drugs may give rise to extensively drug- resistant tuberculosis (XDR-TB). Thus, the rapid detection of drug resistance is vital;, however, the current standard drug susceptibility tests (DST) may take up to 12 weeks raising an alarming concern.² A study was done in China by Li Wan et al, on the accuracy of the reverse dot blot hybridization assay (RDBH) for rapidly detecting the resistance of four anti TB drugs (rifampicin (RIF), isoniazid (INH), streptomycin (SM) and ethambutol (EMB)) in mycobacterium tuberculosis (MTB) isolates.³ Continuous...